How future science educators view themselves and their profession: A study of pre-service science STEM educators - Sheffield, Rachel; Blackley, Susan; Bennett, Dawn (Australian Institutes for Educational Research, 2020)
Attrition of up to thirty per cent in the initial years of a teaching career has led to a high level of disillusionment in teaching as a desirable and rewarding profession. Although many nations have responded with substantial investments in pre-service teacher education, these efforts have failed to dissuade newly qualified teachers from leaving the profession. An important factor in professional membership is a sense of identity to both a particular group of people and a set of established practices. This article examines the initial identity of pre-service science teachers who belong to the science, technology, engineering and mathematics (STEM) cohort of teachers in the primary and secondary initial education programs at an Australian university. We consider the alignment of participants’ initial professional identity, including career commitment, with their concerns about entering the teaching profession. Recommendations are made for actions that might reduce the early career exodus.